Tensile Tests on Four Layers CSM600 Glass Fibers-reinforced Polylite 440-M888 Polyester Resin. (2015) - Modrea, Arina; Teodorescu, Florin; Rosu, Dorin
Abstract: This paper presents basic failure modes encountered in four layers glass fibers-reinforced polyester resin specimens subjected to tensile tests until final collapse. Chopped strand mat CSM600 (600 g/m2 specific weight) has been used to reinforce Polylite 440-M888 polyester resin. From a cured plate manufactured at Compozite Ltd, specimens have been cut using a diamond powder mill to avoid introducing supplementary internal stresses in the laminate. First failures modes occurred at 0.012 strain value. Basic mechanical properties such as Young's modulus, tensile strength, load at maximum load, extension at maximum load and other important features have been experimentally determined on a "LS100 Plus" Lloyd Instruments materials testing machine.